A. M. Samoilenko’s numerical-analytic method without determining equation
We suggest a modification of A. M. Samoilenko’s numerical-analytic method for investigating the problem dx/dt=f(t,x), L(x) = d (here L(x): C([0, T], R^n) → R^n is a linear continuous operator